2017
DOI: 10.1007/s10517-017-3725-y
|View full text |Cite
|
Sign up to set email alerts
|

Level of Interleukins IL-6 and IL-15 in Blood Plasma of Mice after Forced Swimming Test

Abstract: We measured the concentrations of IL-6 and IL-15 in blood plasma of mice at different terms after forced swimming, taking into account exercise intensity and preliminary training. It was shown that training was an important factor affecting blood plasma level of IL both at rest and after single forced swimming: in trained animals, the concentration of both myokines increased immediately after swimming, while in untrained animals, this increase was observed only after 5 h. Changes in cytokine production against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…Our data solely demonstrates that levels of IL-6 are increased in the of paw of mice subjected to swimming, and treatment with pVNS was able to reduce the higher IL-6 levels found in the swimming only group. Consistent with our findings, data from literature have demonstrated an increased level of this cytokine in the circulation of animals subjected to swimming-induced stress ( Kapilevich et al, 2017 ), and also in the muscle of mice subjected to swimming exercise ( Hojman et al, 2019 ). We also found that swimming exercise combined with pVNS reduced the concentrations of IL-10 in the spinal cord.…”
Section: Discussionsupporting
confidence: 93%
“…Our data solely demonstrates that levels of IL-6 are increased in the of paw of mice subjected to swimming, and treatment with pVNS was able to reduce the higher IL-6 levels found in the swimming only group. Consistent with our findings, data from literature have demonstrated an increased level of this cytokine in the circulation of animals subjected to swimming-induced stress ( Kapilevich et al, 2017 ), and also in the muscle of mice subjected to swimming exercise ( Hojman et al, 2019 ). We also found that swimming exercise combined with pVNS reduced the concentrations of IL-10 in the spinal cord.…”
Section: Discussionsupporting
confidence: 93%
“…The serum level of interleukins IL-6 and IL-15 can also be regarded as an indicator of a depressive state in animals, and provides a novel pathway for depression therapy [90]. Over the last three years, the FST has been used as the main test for evaluating both the modelling and drug-therapeutic efficiency.…”
Section: Behavioral Testsmentioning
confidence: 99%
“…According to the authors, IL-6 increases in a delayed manner as it is considered a factor of energy supply. In addition, this cytokine induces fat cleavage and oxidation and participates in the maintenance of glucose homeostasis during exercise (Kapilevich et al, 2017). The kinetics of IL-6 and IL-15 in untrained animals and their delayed effects demonstrate that these cytokines are responsible for the restoration of energy and the overcompensation process.…”
Section: Discussionmentioning
confidence: 99%
“…The kinetics of IL-6 and IL-15 in untrained animals and their delayed effects demonstrate that these cytokines are responsible for the restoration of energy and the overcompensation process. In trained animals the role of these cytokines is to provide the necessary energy to the muscle according to the increase in training loads and increase in intensity (Kapilevich et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation